Workforce Transformation and SME Performance: The Mediating Role of ICT Utilisation - Izzah Sarirotun Nijwah; Keke Tamara Fahira; Tina Rahayu (Universitas Muhammadiyah Semarang, 2026)
This study aims to examine the effect of workforce transformation on SME performance with ICT utilisation as a mediating variable. A quantitative research approach was employed using survey data collected from 119 SME owners. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results indicate that workforce transformation has a significant positive effect on ICT utilisation. Furthermore, ICT utilisation significantly improves SME performance. The findings also show that workforce transformation directly enhances SME performance. In addition, ICT utilisation partially mediates the relationship between workforce transformation and SME performance. These results suggest that the development of workforce capabilities and adaptability plays an important role in supporting the effective utilisation of digital technologies and improving SME performance. This study highlights the importance of strengthening workforce competencies, particularly digital skills, to support digital transformation in SMEs. Future research is recommended to involve larger samples and explore additional organizational factors that may influence SME performance.